Modern weapons and military equipment for issue 4/2013 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Russian exoskeleton "Egzoatlet"U.S. Army offered a self-propelled robot - a machine gunNewspapers in urban warfareHaris "screened tablet""Prism" and the American concept of cyber warfare